Pola Pengintegrasian Pembelajaran Komponen Kebahasaan Kurikulum Tingkat Satuan Pendidikan (KTSP) Mata Pelajaran Bahasa dan Sastra Indonesia SMA/MA - Nurizzati Nurizzati (Fakultas Bahasa dan Seni UNP, 2009)
The formulation of competence standard and basic competence for Indonesian language and literature subject is based on four aspects of language skills. But when viewed from the point of the communicative approach in language learning. generally those competencies do not directly address the language components which must be taught again and teacher often do not specify clearly these aspects when developing indicators of basic integrate the three components of learning, namely :1. mastery of language knowledge which also includes a significant mastery of linguistic rules; 2. Four aspects of language skills (listening, speaking, reading, and writing); 3. A positive attitude towards meaningful Indonesian language and literature which enable student to use language appropriately. Communicative approach in learning the language is emphasized also that language learning is not learning about the language, but learning the language. However, learning the language without learning the rules of language is useless. Therefore, this article would like to try to criticize the imbalance of attention to good language trainings in the four aspects of language skills, supported by a situation that requires students to speak with the correct behavior Key words: Standar kompetensi, kompetensi dasar, pembelajaran bahasa, pendekatan komunikatif, pola pengintegrasian.